2014
DOI: 10.1002/mds.25846
|View full text |Cite
|
Sign up to set email alerts
|

What can biomarkers tell us about cognition in Parkinson's disease?

Abstract: Cognitive decline is common in Parkinson's disease (PD), even in the early motor stage, and this non-motor feature impacts quality of life and prognosis tremendously. In this article, we discuss marker candidates for cognitive decline in PD from different angles, including functional and structural imaging techniques, biological fluid markers in cerebrospinal fluid, and blood genetic predictors, as well as gait as a surrogate marker of cognitive decline. Specifically, imaging-based markers of cognitive impairm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 136 publications
(233 reference statements)
1
48
1
1
Order By: Relevance
“…Evidence that motor changes precede cognitive changes is common in older adults 38 and has fueled an interest in the role of gait as a clinical biomarker of cognitive decline. 6 The shared pathologic mechanisms of gait and cognitive decline support the potential of gait characteristics as clinical biomarkers of cognitive decline in PD 14,39 and work is under way investigating this.…”
Section: Postural Controlmentioning
confidence: 96%
See 1 more Smart Citation
“…Evidence that motor changes precede cognitive changes is common in older adults 38 and has fueled an interest in the role of gait as a clinical biomarker of cognitive decline. 6 The shared pathologic mechanisms of gait and cognitive decline support the potential of gait characteristics as clinical biomarkers of cognitive decline in PD 14,39 and work is under way investigating this.…”
Section: Postural Controlmentioning
confidence: 96%
“…5 CSF proteins (e. g., b-amyloid [Ab] 40 and Ab42; total and p-tau 181 ), traditionally biomarkers of dementia and dementia risk, [6][7][8][9] have also been implicated in motor impairment, highlighting a role for pathologic protein accumulation other than Lewy body and PD-specific a-synuclein (aSyn). Crosssectional studies in early and advanced PD show an association between CSF biomarkers and postural instability and gait (PIGD) phenotype.…”
mentioning
confidence: 99%
“…The risk of dementia is about 80% for the patients living for more than 20 years with PD (Hely et al, 2008). Early and correct identification of the patients with the risk of severe cognitive decline is a challenging problem of neurology, which has led to the suggestion of various markers of cognitive decline in PD (Mollenhauer et al, 2014). Quantitative electroencephalography (qEEG) – digital processing of EEG recordings to obtain numerical and graphical data – showed that the power (the square of amplitudes of electrical activity) of the brain in PD patients with cognitive impairment is increased in the frequency range below 8 Hz, and decreased in the range above 8 Hz (Caviness et al, 2007; Fonseca et al, 2009; Babiloni et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Forty-two percent of patients with Parkinson's disease showed senile plaques and neurofibrillary tangles in the cerebral cortex [14]. Fourth, the level of cerebrospinal biomarkers such as Amyloid-beta and Tau protein is changed in both degenerative diseases and the levels have a correlation with the severity of cognitive impairment in Parkinson's disease [15]. Pathological studies suggest two kinds of pathological changes related to cognitive decline.…”
Section: Parkinson's Disease and Apolipoprotein Ementioning
confidence: 99%